Salt Spray Testing on the Chloride Resistance of Jointed Concrete - Guoping Li; Feilong Tian; Cai Ren (Journal of Asian Architecture and Building Engineering, 2018)
Joints existing in segmental precast and pouring constructions have poorer performance than the monolithic parts in concrete structures, of which the mechanical behaviors have been studied by many researchers. However, studies related to the durability of concrete rarely focus on joints. The purpose of this study is to compare the chloride resistances between joints and the monolithic parts. Concrete structures are generally under a certain stress state, so unstressed specimens and specimens under compressive and tensile stresses were prepared. Salt spray tests on specimens with different stress states and different joint types were conducted. Based on the test results of chloride profiles, the chloride resistances of the specimens under different stress states were compared. The results indicate that the monolithic part has a better chloride resistance than the joint, no matter what the stress state is. Moreover, the chloride resistances of the different joints also differ greatly.